(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The research aims to estimate the added value of the production outputs of the olive crop (olive oil) from the presses until it reaches the final consumer in the local markets in Nineveh Governorate, and to calculate the revenues and profits, which are preceded by calculating the costs, in addition to diagnosing the internal and external factors of olive oil manufacturing, as the research relied on the data collected through a questionnaire form for a random sample of (5) presses out of a total of (20) presses at a rate of (25%) operating in Nineveh Governorate and diagnosing the problems and obstacles that hinder the manufacturing cycle, in addition to secondary data, as the results indicated that the average total cost of the sample amounted to (474881000) dinars and for one ton it amounted to (7664807) dinars/ton, while the average total added value for pressing one ton of olives (3128210) dinars/ton, while the average net added value (3095929) dinars/ton, so the profits per ton of oil have reached (2335193) dinars/ton, where the revenues of one ton of oil had reached (10,000,000) dinars/ton. Despite the increase in pressing costs, the quantities allocated from the olive crop for pressing increased, which was reflected in the added value that was high and the realization of profits as a result of this increase, accompanied by an increase in the national income. It is concluded from this study that increasing the areas planted with olive trees requires increasing the number of presses to keep pace with the increase in local demand for olive oil, which contributes to raising the value of the local product and selling it at prices that compete with global prices. Therefore, the study recommended promoting the local product in foreign markets by participating in international exhibitions and international markets specialized in the olive oil product.